2005
DOI: 10.1073/pnas.0502604102
|View full text |Cite
|
Sign up to set email alerts
|

Yeast genome-wide screen reveals dissimilar sets of host genes affecting replication of RNA viruses

Abstract: host factors ͉ plus-stranded RNA virus ͉ tomato bushy stunt tombusvirus ͉ virus replication ͉ yeast-knockout strains T he success of viruses as pathogens of humans, animals, and plants depends on the viruses' ability to reprogram the host-cell metabolism to support the infection. The virus-host interaction is more complex than the term ''reprogramming'' suggests because host cells have antiviral defense mechanisms. Identifying host genes that can affect virus replication and the infection process is central to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
273
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(282 citation statements)
references
References 42 publications
8
273
0
1
Order By: Relevance
“…For instance, it has been observed that geminiviruses use host factors, such as the proliferating cell nuclear agent, a DNA polymerase accessory factor, NAC domain protein (SINAC1), a transcription factor, and plant homologs of retinoblastoma protein, to reprogram the host's cell cycle to allow replication of their own genome (Gutierrez, 2000;Gutierrez et al, 2004;Rojas et al, 2005). Likewise, several host factors for Tomato bushy stunt virus, a tombusvirus, and Brome mosaic virus, a bromovirus, have been thoroughly investigated using yeast as an artificial host system (Janda and Ahlquist, 1993;Duggal and Hall, 1995;Ishikawa et al, 1997;Noueiry and Ahlquist, 2003;Panavas et al, 2005;Mas et al, 2006;Serviene et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been observed that geminiviruses use host factors, such as the proliferating cell nuclear agent, a DNA polymerase accessory factor, NAC domain protein (SINAC1), a transcription factor, and plant homologs of retinoblastoma protein, to reprogram the host's cell cycle to allow replication of their own genome (Gutierrez, 2000;Gutierrez et al, 2004;Rojas et al, 2005). Likewise, several host factors for Tomato bushy stunt virus, a tombusvirus, and Brome mosaic virus, a bromovirus, have been thoroughly investigated using yeast as an artificial host system (Janda and Ahlquist, 1993;Duggal and Hall, 1995;Ishikawa et al, 1997;Noueiry and Ahlquist, 2003;Panavas et al, 2005;Mas et al, 2006;Serviene et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study was performed for another plant virus, the tomato bushy stunt virus (TBSV). Interestingly, around 100 genes were also identified in this case [58]. Surprisingly, against all predictions only a low number of genes were found to be common in both studies.…”
Section: Use Of Yeast Systems To Identify Host Factors Affecting Viramentioning
confidence: 95%
“…For instance, a marked alteration of cellular metabolism and an increase in fatty acid biosynthetic pathway have been described upon human cytomegalovirus (HCMV), DENV or HCV infection [1, 5,6,11]. The association of viral multiplication with modulation of host cell factors involved in lipid metabolism is not an exclusive feature of animal viruses, thus, replication and recombination of the plant pathogens tombusviruses has been revealed to rely on host genes involved in lipid metabolism [96][97][98][99]. Representative examples of cellular factors related to lipid metabolism and associated to viral replication are summarized in Table 2.…”
Section: Cellular Lipids Involved In Viral Replication Complex Assemblymentioning
confidence: 99%